1982
DOI: 10.1161/01.atv.2.6.467
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and composition of lipoproteins in blood plasma of the WHHL rabbit. An animal model of human familial hypercholesterolemia.

Abstract: T he Watanabe-heritable hyperlipidemic (WHHL) rabbit is a strain of Japanese rabbit discovered by Watanabe which is characterized by grossly elevated levels of serum cholesterol, phospholipids, and triglycerides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
1

Year Published

1983
1983
1992
1992

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(56 citation statements)
references
References 33 publications
(23 reference statements)
5
50
1
Order By: Relevance
“…25 By contrast, Type III hyperiipoproteinemia-a condition that predisposes to premature atherosclerosis-is characterized by strikingly elevated plasma apo E levels that accumulate in intermediate sized lipoproteins (fraction II). 27 ' M An increased mass of apo E in partially catabolized VLDL, IDL, and LDL is also found in certain animal models of atherosclerosis such as the WHHL rabbit 9 and cholesterol-fed monkeys, dogs, and swine. 12 It has been suggested 29 that apo E-containing intermediate sized lipoproteins are atherogenic by virtue of their capacity to deliver cholesterol to macrophage precursors of atherosclerotic foam cells via surface receptors specifically recognizing apo E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 By contrast, Type III hyperiipoproteinemia-a condition that predisposes to premature atherosclerosis-is characterized by strikingly elevated plasma apo E levels that accumulate in intermediate sized lipoproteins (fraction II). 27 ' M An increased mass of apo E in partially catabolized VLDL, IDL, and LDL is also found in certain animal models of atherosclerosis such as the WHHL rabbit 9 and cholesterol-fed monkeys, dogs, and swine. 12 It has been suggested 29 that apo E-containing intermediate sized lipoproteins are atherogenic by virtue of their capacity to deliver cholesterol to macrophage precursors of atherosclerotic foam cells via surface receptors specifically recognizing apo E.…”
Section: Discussionmentioning
confidence: 99%
“…8 The Watanabe heritable hyperlipidemic (WHHL) rabbit, an animal model of FHH, also has elevated plasma apo E levels. 9 The lipoprotein association of apo E, however, has not been described in this disorder. Apo E is normally a component of VLDL, IDL, and HDL subclasses.…”
mentioning
confidence: 96%
“…In contrast, the absence of a protein identical to intestinal B-48 in human prebeta VLDL, IDL, and LDL weighs heavily against the possibility that this protein is secreted by human liver. Again, the rat may be unusual among mammals in this respect because the VLDL of guinea pigs, 47 rabbits, 48 and monkeys (L.L. Rudel, personal communication) contain no B-48 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…By measuring the binding affinity of VLDL incubated with various amounts of apoE for LDL receptors on human fibroblast, we found that one-half to an equal amount of apoE to VLDL protein is required to obtain a maximal effect (H.M. and N.Y., unpublished data). Because the protein concentration of VLDL in WHHL rabbits is =30 mg/dl (11,27), we decided to inject -=30 mg of apoE.…”
mentioning
confidence: 99%